Urban planning after terrorism. The case of Oslo with focus on the impacts of the terrorist attack on the consideration of security, memorialisation and conservation in urban planning. - Paizs, Franziska (My University, 2014)
Terroranschläge sind nicht nur darauf angelegt, Menschen zu verletzen oder zu töten, sie wollen auch die Zivilisation und Kultur eines Landes treffen, indem sie die gebaute Umwelt, insbesondere Bauwerke von symbolischer Bedeutung angreifen. Untersucht man die Folgen terroristischer Anschläge, erweisen sie sich als einschneidende Ereignisse, die in der Konsequenz eine Befestigung von Architekturen und Veränderungen im Städtebau mit Wirkungen auf den öffentlichen Raum und das Stadtbild implizieren. Wie kann Stadtplanung hier reagieren. Das Gleichgewicht zwischen notwendigen Sicherheitsmaßnahmen und der Bewahrung der Qualitäten von "Freiheit" und "Urbanität" muss sich aus nationalen Politikstilen und einem gewachsenen Selbstbild ergeben. Die Arbeit liefert einen Beitrag zum Thema Terrorismus und seine Folgen für die Stadtplanung. Die umfassende Untersuchung von Oslo gibt einen Überblick über die Zukunft des Regjeringskvartalet besonders unter den Aspekten der öffentlichen Sicherheit, des Bewahrens des kulturellen Erbes, des Denkmalwerts des Ortes, wirtschaftlichen Erwägungen und dem Planungsprozess.

Terrorism is a targeted way to hurt a population but also to destroy and annihilate a part of the civilization by attacking the built environment, especially iconic and symbolic buildings with its values of collective memory and cultural heritage, which is at the latest created by the iconic act of destruction. The resilient city with its integrated plans and programs but also technical, personal or physical security aims to reduce the probability and the dimension of terrorist attacks. The research on that cases shows, that terrorist attacks, their impacts and the overcoming do have a very individual character and will always remain a unique and incisive event where individual redevelopment prove the abnormality of those attacks, even though they increased in number in the last years. The consequence is a trend to hardened architecture and changes in urban design with impacts on public space and the appearances of cities nowadays. However the legal framework and general urban planning policy does not seem to be affected by the attacks. Terrorism is in general a reaction on the policy of the targeted country. The reasons for terrorist attacks are not to be found in the urban planning policy of a country - urban planning therefore is not in charge for combating terrorism, that is to say prevent or ward off terrorist attacks. The balance between security measures and the qualities of "freedom" and "urbanity" depends on the national politic attitude and grown self-image. This publication can give a certain contribution to the topic of terrorism and its impact on urban planning. The comprehensive analysis of Oslo gives a summary about the future of the Regjeringskvartalet with regard to the consideration of factors such as security, cultural heritage, memorial values, economic aspects and planning process design.
Keywords: Stadtentwicklungsplanung; Stadtplanung; Städtebau; Stadtgestaltung; Öffentliche Sicherheit; Denkmal; Planungsprozess; Stadtbild; Terrorismus; Attentat; Stadtzerstörung; Wiederaufbau; Regierungsviertel